Modeling the TTL at Continental Scale for a Wet Season: An Evaluation of the BRAMS Mesoscale Model Using TRO‐Pico Campaign, and Measurements From Airborne and Spaceborne Sensors. Issue 5 (6th March 2018) - Behera, Abhinna K.; Rivière, Emmanuel D.; Marécal, Virginie; Rysman, Jean‐François; Chantal, Claud; Sèze, Geneviève; Amarouche, Nadir; Ghysels, Mélanie; Khaykin, Sergey M.; Pommereau, Jean‐Pierre; Held, Gerhard; Burgalat, Jérémie; et al.
Abstract: In order to better understand the water vapor (WV) intrusion into the tropical stratosphere, a mesoscale simulation of the tropical tropopause layer using the BRAMS (Brazilian version of Regional Atmospheric Modeling System (RAMS)) model is evaluated for a wet season. This simulation with a horizontal grid point resolution of 20 km × 20 km cannot resolve the stratospheric overshooting convection (SOC). Its ability to reproduce other key parameters playing a role in the stratospheric WV abundance is investigated using the balloon‐borne TRO‐Pico campaign measurements, the upper‐air soundings over Brazil, and the satellite observations by Aura Microwave Limb Sounder, Microwave Humidity Sounder, and Geostationary Operational Environmental Satellite 12. The BRAMS exhibits a good ability in simulating temperature, cold‐point, WV variability around the tropopause. However, the simulation is typically observed to be warmer by ∼2.0°C and wetter by ∼0.4 ppmv at the hygropause, which can be partly affiliated with the grid boundary nudging of the model by European Centre for Medium‐Range Weather Forecasts operational analyses. The modeled cloud tops show a good correlation (maximum cross‐correlation of ∼0.7) with Geostationary Operational Environmental Satellite 12. Furthermore, the overshooting cells detected by Microwave Humidity Sounder are observed at the locations, where 75% of the modeled cloud tops are higher than 11 km. Finally, the modeled inertia‐gravity wave periodicity and wavelength are comparable with those deduced from the radio sounding measurements during TRO‐Pico campaign. The good behavior of BRAMS confirms the SOC contribution in the WV abundance, and variability is of lesser importance than the large‐scale processes. This simulation can be used as a reference run for upscaling the impact of SOC at a continental scale for future studies. Key Points: The model depicts the typical variability of temperature and water vapor in the tropical tropopause layer, and the gravity wave properties High modeled cloud tops are observed at the overshooting locations detected by MHS, showing similar variability as GOES‐12 measurements Impact of stratospheric sudden warming occurring in the Arctic is detected in the tropical tropopause layer over South America